-12.11x-10.5=75.6-6.5x

Simple and best practice solution for -12.11x-10.5=75.6-6.5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12.11x-10.5=75.6-6.5x equation:



-12.11x-10.5=75.6-6.5x
We move all terms to the left:
-12.11x-10.5-(75.6-6.5x)=0
We add all the numbers together, and all the variables
-12.11x-(-6.5x+75.6)-10.5=0
We get rid of parentheses
-12.11x+6.5x-75.6-10.5=0
We add all the numbers together, and all the variables
-5.61x-86.1=0
We move all terms containing x to the left, all other terms to the right
-5.61x=86.1
x=86.1/-5.61
x=-15+1/2.8769230769231

See similar equations:

| 12+9m=24m+12 | | y=34-8y-2 | | 6/(6/7)=n | | t=3t^2−4t+6 | | 6/6/7=n | | (t)=3t^2−4t+6 | | 1.5+2y=-1 | | -21/8=3/2v | | 2/3b=-6/5 | | 5y+16=91 | | 6(1+3m)=-8(-2m+5 | | 31=4v-13 | | 3.9y=18.34 | | X+0=x+4 | | 4(y-2)=3(y-5) | | 17g-23=130 | | (10x-22)=180 | | 6+18m=-16m-36 | | -5(x+5)=-5x-25 | | 0.3x+0.85x-2=2.6 | | 27=-3x+12 | | -16x^2+18x+6=0 | | 8d+18=74 | | 3t^2-23t+56=0 | | 22+3z=91 | | -3.2w-2=-4 | | -9x=4+7x | | 3*4/5=n | | (2x+12)÷7=6.5 | | 2g-27=9 | | 62+4(x-2)+5x-7=180 | | 7-5m=1-6m |

Equations solver categories